The Impact of Hybrid Working in the Post-Pandemic Covid19 on Employee Job Satisfaction through Work-Life Balance and Workload in Indonesia Leading Heavy Equipment Company - Budiman, Nurdiansyah; Hidayat, Nila K.; Basbeth, Firdaus (Budapest International Research and Critics University, 2022)
The Covid-19 pandemic disrupts many aspects of life. Over the last few years, our behavior has needed to adapt to a new normal. One of the most observable changes due to the COVID-19 pandemic is the implementation of teleworking or a work from home policy. Many companies take the initiative of workplace alignment with new hybrid working methods to face post-pandemic Covid19 to stay productive and relevant to a business challenge. The purpose of this study was to fill the gaps by investigating several potential predictors of job satisfaction during hybrid working implementation in the post-pandemic COVID-19, such as work-life balance and workload. Using quantitative explanatory research methodology, 138 employees from Indonesia's leading heavy equipment company experiencing hybrid working participated. The responses were analyzed using Smart-PLS software to create the Structural Equation Model (SEM). The study revealed that hybrid working has a significant effect directly on work-life balance and workload. It also indirectly affects job satisfaction through work-life balance (full mediation). On the other hand, hybrid working does not directly and insignificantly affect job satisfaction as well as workloads that cannot mediate hybrid working on job satisfaction (no mediation). In the post-pandemic period, hybrid working as a new way of working can maintain employee job satisfaction in the current work environment. In response to future business challenges, hybrid working may be a viable alternative for boosting organizational productivity.